Building policy capacity of local governments for big data applications in public transportation - Ng, Anne Clarice L.; Perez, Revka E.; Tiglao, Noriel Christopher C. (2020)
Policy capacity—defined as the set of skills, resources, and capabilities necessary to perform policy functions—focuses on the managerial and organizational abilities to inform policy decisions with sound research and analysis and to facilitate policy implementation with operational efficiency. In June 2017, the Department of Transportation issued the Omnibus Franchising Guidelines, which set new guidelines for the issuance of franchise for road-based public transport services. It devolved the function of route planning to the local government units (LGUs) within their respective territorial jurisdiction and required the preparation of Local Public Transport Route Plan as a prerequisite. The policy capacity of local governments to address the complex public transportation planning and franchising problem in their respective areas has emerged as a major concern. The study aims to review and evaluate, using the policy capacity framework, the current capabilities of Pasig City in applying big data principles and techniques in transport planning. It particularly documents the experience of the City Transport Development and Management Office. Initial evaluation indicates that the local government possesses readiness and holds great potential in developing big data applications for local public transport planning and management. The results may help LGUs further improve and fine-tune their capacity for using big data, through which their overall policy capacity may be improved.
Keywords: Transportation management systems -- Pasig City; Local government -- Transportation management; Traffic engineering -- Pasig City; Transportation policy; Transportation -- Computer network resources; Traffic engineering; Big data